Improving Nurses' Behavioral Health Knowledge and Skills With Mental Health First Aid. Issue 4 (July 2019) - Baker, Margaret W.; Dower, Catherine; Winter, Peggi Banahan; Rutherford, Marcella M.; Betts, Virginia Trotter
Abstract : Given the current professional behavioral health workforce shortage, nursing professional development practitioners require educational resources to fully support registered nurses across settings in responding to patients with behavioral health symptoms. Mental Health First Aid is an 8-hour training to help nonprofessional bystanders assess a mental health crisis, provide initial help, and connect to supports and self-help resources in the local community. Mental Health First Aid was acceptable and useful to 60 RNs and can be supplemented with additional content.